2013
DOI: 10.1088/0268-1242/28/5/053001
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of sexi-thiophene and para-hexaphenyl and its implications for the fabrication of self-assembled lasing nano-fibres

Abstract: Over the last few years, epitaxially grown self-assembled organic nano-structures became of increasing interest due to their high potential for implementation within opto-electronic devices. Exemplarily, the epitaxial growth of the rod-like molecules para-hexaphenyl (p-6P) and α-sexi-thiophene (6T) is discussed within this review. Both molecules tend to crystallize in highly asymmetric elongated entities which are also called nano-fibres. It is demonstrated that the obtained needle orientations and morphologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 225 publications
3
93
1
Order By: Relevance
“…[49][50][51] For instance, Campione and co-workers [ 52 ] showed that the homoepitaxy of T6 is reduced by increasing temperature, at which even needles of lying molecules can form, indicating that the differences in free energy between the possible orientations are small, as well acknowledged for organic-organic epitaxy. [ 31,53,54 ] Interestingly, in reference [ 52 ] it was also observed a roughening at (100) terrace edges upon increasing temperature, which was attributed to desorption, but that in the light of the present results it could be also related to the peculiar shape of islands, as discussed above. Indications of a reduced interlayer correlation in T6 fi lms grown on SiO 2 are also provided by Raman scattering measurements, in which lattice phonons polarized in the direction perpendicular to molecular layers are not found for thicknesses lower than 10 ML, [ 50 ] while conversely grazing incidence X-ray experiments showed that a layered structure still exists.…”
Section: Ml)supporting
confidence: 71%
“…[49][50][51] For instance, Campione and co-workers [ 52 ] showed that the homoepitaxy of T6 is reduced by increasing temperature, at which even needles of lying molecules can form, indicating that the differences in free energy between the possible orientations are small, as well acknowledged for organic-organic epitaxy. [ 31,53,54 ] Interestingly, in reference [ 52 ] it was also observed a roughening at (100) terrace edges upon increasing temperature, which was attributed to desorption, but that in the light of the present results it could be also related to the peculiar shape of islands, as discussed above. Indications of a reduced interlayer correlation in T6 fi lms grown on SiO 2 are also provided by Raman scattering measurements, in which lattice phonons polarized in the direction perpendicular to molecular layers are not found for thicknesses lower than 10 ML, [ 50 ] while conversely grazing incidence X-ray experiments showed that a layered structure still exists.…”
Section: Ml)supporting
confidence: 71%
“…On the other hand, the anisotropic character of the COMs allows them to self-assemble into a variety of structures each characterized by different features in terms of functionality (charge transfer, optimization of band-gaps, excitation transfer). Combining these materials thus leads to tunable hybrids whose characteristic properties, such as the work-function and charge carrier mobility, can be tailored through the choice molecules and substrates [1][2][3], as well as through the self-assembled structures formed by the adsorbed molecules [4][5][6]. This wide range of possibilities could not be achieved with an organic or inorganic component alone.…”
Section: Introductionmentioning
confidence: 99%
“…Thin film growth control is also a central issue in organic electronics [19], because the intrinsic film properties as well as the formed interfaces significantly determine the device performance [20][21][22]. Especially, the use of Gr as possible transparent and mechanically flexible * This paper was presented at the 12th International Conference on Atomically Controlled Surfaces, Interfaces and Nanostructures (ACSIN-12) in conjunction with the 21st International Colloquium on Scanning Probe Microscopy (ICSPM21), Tsukuba International Congress Center, Tsukuba, Japan, November 4-8, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…An intensively studied model system for organic thin film growth on solid surfaces is parahexaphenyl (6P) [23][24][25][26][27][28][29][30]. The rodlike, conjugated 6P molecule (C 36 H 24 ) crystallizes in a herringbone bulk structure [31] and exhibits a gap of ∼3.1 eV between its lowest unoccupied molecular orbital and the highest occupied molecular orbital which makes it suitable for OLED applications [22]. So far, a few studies have been dedicated to the growth of 6P on Ir(111) supported Gr [32,33].…”
Section: Introductionmentioning
confidence: 99%